Pengembangan Instrumen Tes Untuk Mengukur Kemampuan Berfikir Kreatif Matematis dengan Bantuan Wordwall Dalam Materi Relasi dan Fungsi Kelas VIII SMP Negeri 2 Sintang - Neke Adriana Neke; Muhamad Firdaus; Wandra Irvandi (LPD Universitas PGRI Pontianak, 2026)
Abstract: This study aimed to develop a Wordwall-assisted test instrument to measure students’ mathematical creative thinking skills on the topic of relations and functions for eighth-grade students at SMP Negeri 2 Sintang, and to determine its validity, practicality, and effectiveness. The research employed a Research and Development (R&D) method using a 3D development model consisting of the define, design, and development stages. The research subjects included three material experts, three media experts, and 28 students of class VIII E at SMP Negeri 2 Sintang in the 2025/2026 academic year. Data were collected through validation sheets, teacher and student response questionnaires, and a mathematical creative thinking skills test. Data analysis was conducted to determine the validity, practicality, and effectiveness of the developed product. The results showed that the developed Wordwall-assisted test instrument met the criteria of being highly valid, highly practical, and effective. The validity level, based on assessments by material and media experts, obtained an average percentage of 87.95%, categorized as highly valid. The practicality level, based on teacher and student response questionnaires, obtained an average percentage of 88.86%, categorized as highly practical. The effectiveness level was determined from students’ post-test results, where 20 out of 28 students achieved learning mastery, resulting in a mastery percentage of 71.43%, which falls into the effective category. Therefore, the Wordwall-assisted test instrument on the topic of relations and functions is feasible to be used as an evaluation tool for measuring the mathematical creative thinking skills of eighth-grade students at SMP Negeri 2 Sintang. Keywords: Test Instrument, Wordwall, Mathematical Creative Thinking Skills, Relations and Functions.